The functional connectivity between dorsal-medial prefrontal cortex and middle cingulate cortex links trait rumination and depressive symptoms - Yinghui Guo; Dongtao Wei (PLoS ONE, 2025)
Task-based functional neuroimaging has revealed that rumination is associated with functional activations in the default mode network (DMN). The present study aimed to examine whether resting state functional connectivity (FC) within the DMN is associated with individual differences in trait rumination. Using the seed-based functional connectivity analysis in a relatively large sample of late adolescents, this study investigated the neural correlates of trait rumination and their associations with depressive symptoms. Results showed that higher functional connectivity between the left dorsal medial prefrontal cortex (DMPFC) and middle cingulate cortex (MCC) was positively associated with trait rumination. Additionally, stronger FC between the left DMPFC and the right inferior parietal lobe (IPL) was also related to trait rumination. Furthermore, logistic regression analysis indicated that FC strength between the left DMPFC and MCC was significantly associated with depressive symptom severity. These findings suggest DMPFC-related network may reflect neural mechanisms linked to both trait rumination and depressive symptoms in late adolescence.